Up‐regulation of the mammalian target of rapamycin complex 1 subunit Raptor by aldosterone induces abnormal pulmonary artery smooth muscle cell survival patterns to promote pulmonary arterial hypertension. Issue 7 (22nd March 2016) - Aghamohammadzadeh, Reza; Zhang, Ying‐Yi; Stephens, Thomas E.; Arons, Elena; Zaman, Paula; Polach, Kevin J.; Matar, Majed; Yung, Lai‐Ming; Yu, Paul B.; Bowman, Frederick P.; Opotowsky, Alexander R.; Waxman, Aaron B.; et al.
ABSTRACT: Activation of the mammalian target of rapamycin complex 1 (mTORC1) subunit Raptor induces cell growth and is a downstream target of Akt. Elevated levels of aldosterone activate Akt, and, in pulmonary arterial hypertension (PAH), correlate with pulmonary arteriole thickening, which suggests that mTORC1 regulation by aldosterone may mediate adverse pulmonary vascular remodeling. We hypothesized that aldosterone‐Raptor signaling induces abnormal pulmonary artery smooth muscle cell (PASMC) survival patterns to promote PAH. Remodeled pulmonary arterioles from SU‐5416/hypoxia‐PAH rats and monocrotaline‐PAH rats with hyperaldosteronism expressed increased levels of the Raptor target, p70S6K, which provided a basis for investigating aldosterone‐Raptor signaling in human PASMCs. Aldosterone (10 ‐9 to 10 ‐7 M) increased Akt/mTOR/Raptor to activate p70S6K and increase proliferation, viability, and apoptosis resistance in PASMCs. In PASMCs transfected with Raptor‐small interfering RNA or treated with spironolactone/eplerenone, aldosterone or pulmonary arterial plasma from patients with PAH failed to increase p70S6K activation or to induce cell survival in vitro. Optimal inhibition of pulmonary arteriole Raptor was achieved by treatment with Staramine‐monomethoxy polyethylene glycol that was formulated with Raptor‐small interfering RNA plus spironolactone in vivo, which decreased arteriole muscularization and pulmonary hypertension in 2 experimental animal models of PAH in vivo. Up‐regulation of mTORC1 by aldosterone is a critical pathobiologic mechanism that controls PASMC survival to promote hypertrophic vascular remodeling and PAH.—Aghamohammadzadeh, R., Zhang, Y.‐Y., Stephens, T. E., Arons, E., Zaman, P., Polach, K. J., Matar, M., Yung, L.‐M., Yu, P. B., Bowman, F. P., Opotowsky, A. R., Waxman, A. B., Loscalzo, J., Leopold, J. A., Maron, B. A. Up‐regulation of the mammalian target of rapamycin complex 1 subunit Raptor by aldosterone induces abnormal pulmonary artery smooth muscle cell survival patterns to promote pulmonary arterial hypertension. FASEB J. 30, 2511‐2527 (2016). www.fasebj.org